Teologi Pengilhaman dalam Perspektif Alkitab: Menanggapi Tantangan Ajaran-Ajaran Palsu Tentang Allah - Cintya Fioni; Deden Andika Saputra; Fitri Fitri; Sarmauli Sarmauli (Jurnal Magistra, 2024)
Based on the study and understanding that the Bible is God's Word which is the foundation of faith for every believer to be able to provide life transformation to glorify Christ in church life, this research will examine and formulate theologically inspiration from a Biblical perspective in responding to the challenges of false teachings about God. The result achieved through a literary approach is that the Bible is the Word of God inspired by the Holy Spirit which also inspired writers to proclaim the news about the Kingdom of God for mankind. Apart from that, the Bible is used as a benchmark for preaching the Word in church life. The implication for the reformatory church is that the church must return to the Bible just as the reformers thought in accordance with the Sola principle.